Respirometric balance and analysis of four microalgae : Dunaliella Tertiolecta, Chlorella Vulgaris, Spirulina Platensis and Botryococcus Braunii - Sydney, Eduardo Bittencourt (2009)
Orientador: Prof. Dr. Carlos Ricardo Soccol